2009
DOI: 10.4314/wajae.v11i1.45722
|View full text |Cite
|
Sign up to set email alerts
|

Correlating biochemical and chemical oxygen demand of effluents – A case study of selected industries in Kumasi, Ghana

Abstract: The study aims at establishing an empirical correlation between biochemical oxygen demand (BOD 5 ) and chemical oxygen demand (COD) of effluents from selected industries in the Kumasi Metropolis to facilitate speedy effluent quality assessment or optimal process control. Hourly effluent samples were collected for an 8-h period three times per week for analysis of the principal parameters BOD 5 and COD, using the Standard Methods for the Examination of Water and Wastewater. Measured BOD 5 and COD of the efflue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 3 publications
1
22
0
2
Order By: Relevance
“…There a lot of investigations on the effect of inoculation and subsequent transfer of cata-bolic genes on in situ biodegradation in soils and bioreactors as demonstrated in the present study, such as: Di Giovanni et al 38 demonstrated transfer of the IncP-1L plasmid pJP4 from Ralstonia eutropha JMP134 to indigenous soil bacteria when high concentrations of 2,4- Diya'uddeen et al 30 reported that the minimum amount of dissolved oxygen necessary for normal life in an aquatic environment is about 2 mg/L, 41 and the discharge of high organic matter containing waste waters into water bodies results in the excess consumption of oxygen by the bacteria. This is oxidation of the effluent, thus depleting oxygen from the water faster than it dissolves back into the water from the air.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…There a lot of investigations on the effect of inoculation and subsequent transfer of cata-bolic genes on in situ biodegradation in soils and bioreactors as demonstrated in the present study, such as: Di Giovanni et al 38 demonstrated transfer of the IncP-1L plasmid pJP4 from Ralstonia eutropha JMP134 to indigenous soil bacteria when high concentrations of 2,4- Diya'uddeen et al 30 reported that the minimum amount of dissolved oxygen necessary for normal life in an aquatic environment is about 2 mg/L, 41 and the discharge of high organic matter containing waste waters into water bodies results in the excess consumption of oxygen by the bacteria. This is oxidation of the effluent, thus depleting oxygen from the water faster than it dissolves back into the water from the air.…”
Section: Resultsmentioning
confidence: 83%
“…This is oxidation of the effluent, thus depleting oxygen from the water faster than it dissolves back into the water from the air. 41 In addition, oxygen availability is important because the end products of chemical and biochemical reactions in anaerobic systems often produce aesthetically displeasing colours, tastes and odours in water. 8 Phenol is one of the major pollutants found in refinery effluents.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation of effluent by bacteria results in depletion of oxygen in water, faster than oxygen gain from air. This problem leads to inadequate maintenance of higher life forms [10]. Additionally, wastewater consisting excessive amount of fats and oils can cause the formation of surface films and shoreline deposits and can lead to environmental degradation when discharged to water media [11].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…In aquatic environments, the minimum amount of dissolved oxygen for normal life is about 2 mg/L [3]. The discharge of wastewater containing dyes into water bodies can result in depleting oxygen and production of toxic sub products, such as hydrogen sulphide (H 2 S).…”
Section: Introductionmentioning
confidence: 99%